2015
DOI: 10.17140/semoj-1-101
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of High-Cut Shoes, Running Shoes and Prophylactic Supports on Ankle Stability When Performing a “V”-Cut Movement

Abstract: CitationCommons AT, Low DC. Understanding the effect of high-cut shoes, running shoes and prophylactic supports on ankle stability when performing a "v"-cut movement. Research ABSTRACTAnkle inversion injury is extremely common in basketball, whereby rearfoot inversion and ankle plantar flexion is greater in those with injury. The current study analysed the response of recreational basketball players to three different footwear conditions; high-cut basketball shoe, low-cut running shoe and low-cut running shoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…The biomechanical analyses examining the effects of high cut footwear have provided contradictory results. In 45° cutting movements Commons & Low (16) showed that high-cut footwear increased the peak ankle inversion angle whereas Lam et al, (15) and Liu et al, (17) found that the ankle inversion angle and peak inversion velocity were reduced in high-cut footwear. In addition, Klem et al, (18) showed during a 45° cutting movement that a hinged ankle brace reduced peak inversion, dorsiflexion and compressive loading compared to no-brace.…”
Section: Introductionmentioning
confidence: 96%
“…The biomechanical analyses examining the effects of high cut footwear have provided contradictory results. In 45° cutting movements Commons & Low (16) showed that high-cut footwear increased the peak ankle inversion angle whereas Lam et al, (15) and Liu et al, (17) found that the ankle inversion angle and peak inversion velocity were reduced in high-cut footwear. In addition, Klem et al, (18) showed during a 45° cutting movement that a hinged ankle brace reduced peak inversion, dorsiflexion and compressive loading compared to no-brace.…”
Section: Introductionmentioning
confidence: 96%